THE EFFECT OF COMPENSATION, LEADERSHIP, WORK ENVIRONMENT, AND TRAINING ON EMPLOYEE PERFORMANCE OF BANK SYARIAH MANDIRI MANADO - Laksmana, Danang Afif; Lapian, S.L.H.V. Joyce; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
In this globalization era, many investors are willing to invest in Indonesia, and human resource is the main problem that Indonesian people have. Human Resource Department is very important, because they control the company’s employee, they choose the right employee to work for the company, and they arrange the employee compensation, training, and sometimes workplace of the employee–work environment. The purpose of this study is to find out the effect of compensation, leadership, work environment, and training on employee performance of Bank Syariah Mandiri in Manado. This research collects data through questionnaires and uses Multiple Regressions. Population observed is the employee of Bank Syariah Mandiri with 30 respondents as the sample size. The result of this study shows that compensation and work environment have significant positive effect on employee performance, while leadership and training have positive influence but no significant effect on employee performance. To increase the performance of employee, the recommendation for Bank Syariah Mandiri are to maintain fair compensation and good work environment for their employee, also make a better training program for employee and the leader must improve their motivational skill to encourage their employee. Keywords: compensation, employee performance, leadership, training, and work environment